Ethnomathematics-Based Animated Video on Geometry Material to Improve Mathematical Literacy and Learning Resilience of Second Grade Students - Ni Putu Dian Amhira Wijaya; Komang Surya Adnyana; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2025)
The low mathematical literacy and learning resilience of elementary school students, especially in geometry material, is a challenge in learning in lower grades. This study aims to develop and test the effectiveness of ethnomathematics-based animation videos in improving mathematical literacy and learning resilience of grade II students. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 23 grade II elementary school students. In this development research, there are two types of data, namely qualitative data and quantitative data. The data collection methods and instruments used to obtain data and information from this study used questionnaires and tests. The results of the study showed that ethnomathematics-based animation videos were effective in improving mathematical literacy and forming students' learning resilience attitudes. This media is also considered interesting, easy to understand, and relevant to students' local culture. The implications of this study indicate the importance of developing contextual learning media based on local culture to improve the quality of mathematics learning in elementary schools.